2022
DOI: 10.2196/37034
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of 3D Total-Body Photography to Monitor Nevi: Results From an Australian General Population-Based Cohort Study

Abstract: Background Digital 3D total-body photography of the skin surface is an emerging imaging modality that can facilitate the identification of new and changing nevi. Objective We aimed to describe the experiences of study participants drawn from the general population who were provided 3D total-body photography and dermoscopy for the monitoring of nevi. Methods A population-based prospective study of adults aged… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Since 3D total‐body photography is a relatively novel dermatological imaging technique, 3,4,13 little is known about consumers' perceptions of the technology. A recent study by our group 14 explored participants' experiences of 3D total‐body photography over a 3‐year period, collecting participant feedback ( n = 149) at the halfway study timepoint (18‐months) and final study timepoint (36‐months). At both timepoints, 69% stated they completely trusted 3D total‐body photography, with over 90% reporting they were comfortable with the technology and would consider using it again in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 3D total‐body photography is a relatively novel dermatological imaging technique, 3,4,13 little is known about consumers' perceptions of the technology. A recent study by our group 14 explored participants' experiences of 3D total‐body photography over a 3‐year period, collecting participant feedback ( n = 149) at the halfway study timepoint (18‐months) and final study timepoint (36‐months). At both timepoints, 69% stated they completely trusted 3D total‐body photography, with over 90% reporting they were comfortable with the technology and would consider using it again in the future.…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the study, almost all participants (99%) perceived 3D total‐body photography to be a useful tool that can improve the diagnosis and monitoring of skin lesions. Our previous study 14 details consumer experiences after actual use, while the current study provides insight into consumer perceptions of the technology prior to undergoing 3D total‐body photography. Differences in consumer acceptance and perceptions of dermatology technology before and after practical experience are common, with acceptance generally decreasing after use 15 .…”
Section: Discussionmentioning
confidence: 99%
“…An Australian prospective cohort study of 3D total‐body photography for monitoring naevi in the general population ( n = 149) found high levels of comfort and satisfaction after use of the technology 4 . In their research setting, the main barriers identified were trust in the diagnosis, followed by physical privacy (the requirement to undress and be photographed in their underwear), cost and travel requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced technology allows the experienced clinician to identify changes in existing nevi. The 3D TBP imaging system utilizes software that presents the number, border, irregularity, and color distribution of nevi and other skin lesions (Horsham et al, 2022). Studies using TBP and dermoscopy (including FIGURE 1.…”
mentioning
confidence: 99%
“…Total body photography evolved from two-dimensional (2D) imaging with the ability to create a 3D representation of the patient linked with dermoscopy images of individual lesions (Horsham et al, 2022). 3D TBP launched with improved imaging capabilities via 92 cameras and white or cross-polarized lighting (Rayner et al, 2018).…”
mentioning
confidence: 99%